In Vitro Enamel Remineralization Efficacy of Calcium Silicate-Sodium Phosphate-Fluoride Salts versus NovaMin Bioactive Glass, Following Tooth Whitening - El-Damanhoury, Hatem M.; Elsahn, Nesrine A.; Sheela, Soumya; Bastaty, Talal (European Journal of Dentistry, 2021)
Objectives This study aimed to evaluate the effect of in-office bleaching on the enamel surface and the efficacy of calcium silicate-sodium phosphate-fluoride salt (CS) and NovaMin bioactive glass (NM) dentifrice in remineralizing bleached enamel.Materials and Methods Forty extracted premolars were sectioned mesio-distally, and the facial and lingual enamel were flattened and polished. The samples were equally divided into nonbleached and bleached with 38% hydrogen peroxide (HP). Each group was further divided according to the remineralization protocol (n = 10); no remineralization treatment (nontreated), CS, or NM, applied for 3 minutes two times/day for 7 days, or CS combined with NR-5 boosting serum (CS+NR-5) applied for 3 minutes once/day for 3 days. The average Knoop hardness number (KHN) and surface roughness (utilizing atomic force microscopy) were measured. Surface topography/elemental analysis was analyzed by using scanning electron microscopy/energy dispersive X-ray analysis. All the tests were performed at baseline, after bleaching, and following each remineralization protocol. Data were statistically analyzed by two-way analysis of variance and Bonferroni post hoc multiple comparison tests (α = 0.05).Results HP significantly reduced KHN and increased roughness (p < 0.05). All remineralization materials increased the hardness and reduced the surface roughness after bleaching except NM, which demonstrated significantly increased roughness (p < 0.05). Ca/P ratio decreased after bleaching (p < 0.05), and following treatment, CS and CS+NR-5 exhibited higher remineralization capacity in comparison to NM (p < 0.05).Conclusion Although none of the material tested was able to reverse the negative effect of high-concentration in-office HP on enamel completely, the remineralization efficacy of CS and CS+NR-5 was superior to that of NM.
Keywords: bleaching; enamel; remineralization; scanning electron microscopy; energy dispersive X-ray analysis; calcium silicate-sodium phosphate-fluoride; NovaMin